ANALISIS KESEIMBANGAN LINTASAN UNTUK MENINGKATKAN PROSES PRODUKSI PADA AIR MINERAL DALAM KEMASAN - Ahyadi, Harwan; Saputra, Rudi; Suhartanto, Eko (Bina Teknika, 2015)
Production is an economic activity that adds value by creating and providing goods and services, the creation of products or services and at the same time the creation of value. In economics, production is the act of creating the output, goods or services that have value and contribute to individual utilities.Production line balancing is a very important thing in planning production. Expected to regulate the flow of process efficiency can be achieved optimum production. In addition, the accumulation of intermediate goods from one machine to another machine, thus resulting in increased balance delay. In the process of making drinking water should be done step-by-step production process is handled hygienically, because bottled water products consumed directly by the human body. Drinking water production capacity is 5250 bottles per day, equivalent to 218 boxes, but the target is the company charged, equivalent to 7000 bottles of 291 boxes per day. With the method of determining the regional approach has obtained the standard time of each process for each work station and increase worker productivity, increased production capacities of 218 boxes / day to 295 boxes / day after the repair, companies gain efficiency by 35%